Metabolic profile of obese and non-obese patients with Polycystic Ovary Syndrome - Lopes, Ione Maria Ribeiro Soares (2021)
To evaluate the clinical and metabolic characteristics of women with Polycystic Ovary Syndrome (PCOS) of different phenotypes. Controlled and analytical cross-sectional design. Sampling was non-probabilistic and composed of 120 participants, forming four groups: 1A (without PCOS and normal weight); 1B (without PCOS and with abnormal weight); 2A (PCOS and normal weight) and 2B (PCOS and abnormal weight). Structured form and electronic medical record were used for data collection. Uni and bivariate statistics were performed using IBM® SPSS® 21.0 software. Metabolic syndrome predominated in groups 2A (7.1%) and 2B (37.5%) compared to the respective controls 1A (0%) and 1B (19.2%). Similarly, the insulin was higher in groups 2A (15.7±8.2) and 2B (19.8±6.7) compared to 1A (6.5±4) and 1B (6.5±4,8). The 2-hour oral glucose tolerance test (OGTT) was superior in group 2B (132.1±31.3) compared to group 1B (115.2±20.8) and in group 2A (111.9±24.7) in relation to 1A (105.4±12.1). Total and free testosterone levels were higher in groups 2A (4.4±6.7 and 1.4±1.5, respectively) and 2B (2±2.4 and 1±0.9) in relation to 1A (1,2±3.8 and 0.2±0.3) and 1B (0.5±0.4 and 0.2±0.4). The systolic blood pressure was higher in 2B (125.8±11.7) than 1B (123.3±11.7) and in 2A (122.1±10) compared to 1A (113.7±8,7). PCOS is associated with an unfavorable metabolic profile, with significance for insulin resistance, hyperandrogenism and metabolic syndrome, making essential the broad and multidisciplinary clinical follow-up.